Perbandingan Kemampuan Pemecahan Masalah Matematis Siswa antara yang Belajar Menggunakan Pembelajaran Problem Based Learning Dan Problem Posing - Septian Wulandari (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
The mathematical problem-solving ability of students needs to be supported by the role of the teacher in the learning process of students. However, the learning that takes place in schools generally conducted teacher-oriented. Therefore, the need for learning that is able to facilitate students so that students become active in the learning process. Based on the above presentation, this research was conducted to determine the difference between the problem-solving ability of students to learn to use problem posing with students who learn to use problem-based learning. The sampling technique using a two-stage sampling, the technique purposive sampling and cluster random sampling, as tested homogeneity and normality, then, do equality test on average between classes. The sample measurements validity of using content validity, construct, and empirical. Instrument reliability coefficient is calculated using Cronbach Alpha. Testing normality test at significance level Liliefors? = 0,05. Testing homogeneity with Fisher's test and hypothesis testing was performed using t-test with a significance level ? = 0,05. The result of validity are t_(observe)=3,759 and t_0,95=1,664 , t_(observe)> t_0,95, then reject H_0. It can be concluded that the mathematical problem-solving ability of students to learn by learning problem-based learning is higher than the problem posing. Key Words: Problem Posing, Problem Based Learning, Mathematical Problem Solving